Stage-based treatment for thymoma in due consideration of thymectomy: a single-center experience and comparison with the literature. Issue 1 (December 2015) - Lindenmann, Joerg; Fink-Neuboeck, Nicole; Pichler, Martin; Anegg, Udo; Maier, Alfred; Smolle, Josef; Smolle-Juettner, Freyja
Abstract Background Thymomas represent an uncommon and heterogeneous group of intrathoracic malignancies which require different treatments corresponding to their individual tumor stage. The objective of this study was to review the efficacy of our applied stage-based treatment for thymoma in due consideration of thymectomy. Methods This is a single-center, institutional review board-approved retrospective study of 50 consecutive patients with thymoma treated at our division within 10 years. Results There were 29 women (58 %) and 21 men (42 %), mean age 58.3 years. Twenty nine (58 %) had clinical symptoms and 14 (28 %) had myasthenia gravis. Forty-five patients (90 %) underwent thymectomy and complete resection was done in 42 cases (93.3 %). Histologic results were 6 subtype A, 5 AB, 8 B1, 12 B2, 12 B3, and 7 C. The Masaoka staging system revealed 20 stage I, 18 stage II, 6 stage III, and 6 stage IV. Two patients had neoadjuvant therapy and 25 received postoperative treatment. Five (11.1 %) had tumor recurrence, treated with re-resection. The 5-year disease-free survival was 91.5 %. Two patients died of tumor progression and three died of other causes (10 %). The 5-year overall survival was 82.3 % and the median survival time was 92.1 months. The 5-year survival rate after thymectomy was 87.2 % and the median survival was 92.1 months. Conclusions Complete resection still remains the mainstay in the treatment of non-metastatic thymoma and should be performed whenever feasible. Close multidisciplinary teamwork is mandatory to optimize the neurologic outcome and to prolong postoperative survival.